Efektivitas Pelaksanaan Supervisi Kepala Sekolah Terhadap Standar Proses Pembelajaran Pendidikan Agama Islam di SMA Negeri Unggulan Kabupaten Musi Rawas - Lilis Merlita; Desy Eka Citra Dewi (Jurnal Ilmiah Edukatif, 2023)
Supervision is one of the duties of the school principal to carry out inspections, inspections, supervision and evaluation of the performance of teaching staff in order to make improvements so that quality learning is achieved. Apart from that, the function of supervision as a form of school administration can be seen from the goals to be achieved through assessing the activities carried out at school. Based on this, the principal is very appropriate to become a supervisor because he understands the conditions of the school. The aim of this research is to determine the extent to which the principal's supervision can improve the quality of the Islamic Religious Education learning process at SMAN Musi Rawas Regency. In this research the author used a descriptive method with a qualitative approach. Data collection techniques used were observation, documentation and interviews with school principals. Primary data sources were generated from observation, documentation and interviewing school principals at Sma N Unggulan District. Musi Rawas, and secondary data generated from documents, journals and books. The research results show that the implementation of school principal supervision has had a positive impact on improving the quality of the learning process. Success factors and obstacles in the implementation of supervision are identified, providing valuable insight for the development of more effective supervision strategies in the future. This research contributes to the understanding of the importance of supervision in improving the quality of Islamic Religious Education learning in the high school environment.